Pengaruh Pemberian Paclobutrazol terhadap Pertumbuhan dan Hasil Jagung Manis di Tanah Entisol - Ardianto, Erwin (Jurnal Sains Pertanian Equator, 2019)
The aim of this research was to determine the effect of paclobutrazol on the growth and yield of sweet corn on entisol. This research was conducted at Dusun Banjar Laut, Rasau Jaya 2, Kubu Raya regency, Kalimantan Barat province. This research started on February 14th 2018 to April 21st 2018. The experimental design used was complete block design (CBD) consist of 5 treatment levels concentration of paclobutrazol, namely : 0 ppm (p0); 500 ppm (p1); 1000 ppm (p2); 1500 ppm (p3); dan 2000 ppm (p4). Each treatment was repeated 5 times and each plot consist of 5 plant samples. The variables observed in this research were include height of plant, leaf area, stem diameter, root volume, dry weight of the upper part of the plant, root dry weight, time of anthesis and time of silking, weight of cob per plot, weight of cob with husk, weight of cob without husk, cob length, cob diameter. The results showed that application of paclobutrazol affected the growth and yield of sweet corn on entisol. The application of paclobutrazol gives an effect on height of plant, stem diameter, root dry weight and weight cob sweet corn per plot.Keywords : Entisol , Sweet Corn, Paclobutrazol.